Baseline SYNTAX Score and Long-Term Outcome in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. (November 2015) - Akgun, Taylan; Oduncu, Vecih; Bitigen, Atila; Karabay, Can Yucel; Erkol, Ayhan; Kocabay, Gonenc; Ozveren, Olcay; Yildiz, Abdulmelik; Cimen, Arif Oguzhan; Kirma, Cevat
Objectives: The SYNTAX score (SXscore) has emerged as a reproducible angiographic tool to quantify the extent of coronary artery disease based on the location and complexity of each lesion. The aim of this study was to evaluate whether the SXscore is an independent predictor of long-term cardiovascular outcomes in patients treated with primary percutaneous coronary intervention (PCI) for acute ST-segment elevation myocardial infarction (STEMI). Methods: A total of 2993 patients with acute STEMI who underwent primary PCI were stratified into the 4 groups according to the SXscore quartiles; quartile 1(Q1, SXscore ≤ 9, n = 819), Q2 (9 < SXscore < 16, n = 715), Q3 (16 ≤ SXscore < 20, n = 710), and Q4 (SXscore ≥ 20, n = 749). Results: There were significant differences among the quartiles with respect to age, basal creatinine and glucose levels, and the incidences of diabetes mellitus, Killip ≥2, and anemia. From Q1 to Q4, there were increasing rates of culprit left anterior descending lesion ( P < .001), multivessel disease ( P < .001), chronic total occlusion ( P < .001), and proximal lesion localization ( P < .001). At long-term follow-up, all-cause mortality, nonfatal myocardial infarction, stroke, rehospitalization due to heart failure, and the need of revascularization were significantly more frequent among the patients in the highest SXscore quartile. In multivariate analysis, after including the SXscore as a numerical variable into the model, every point of increase was determined as an independent predictor for long-term mortality (hazard ratio [HR] 1.03, 95% confidence interval [CI] 1.01-1.05, P = .008) and for overall major adverse cardiac events (MACEs; HR 1.02, 95% CI 1.01-1.04, P < .001). Conclusion: The SXscore is an independent predictor of both in-hospital and long-term mortality and MACE in patients with acute STEMI undergoing primary PCI.